Freqüência de raízes fusionadas, separadas divergentes, separadas convergentes, separadas retilíneas e dilaceradas dos terceiros molares. - Nicodemo, R. A.; Medici Filho, E.; de Moraes, L. C.; de Melo Castilho, J. C. (My University, 1990)
In a sample of Brazilian white young adults between 18-23 years old, the A.A. studied the third molar roots, in anatomical aspects, using the orthopantomographic radiographic method. They concluded that the superior third molar shows a biggest number of fusionated roots (19.50% in the right side and 19.66% in the left side) and the inferior third molar shows a biggest number of separated roots (21.48% in the right side and 19.66% in the left side).
Frequency of fused roots, divergent separation, convergent separation, rectilinear separation and delaceration of third molars
Keywords: adult; Brazil; congenital malformation; female; human; male; molar tooth; tooth malformation; tooth root; Adult; English Abstract; Female; Fused Teeth; Human; Male; Molar, Third; Tooth Root